« The arrival of a foreigner and a stranger at my aunt’s house » : l’étrange et l’étranger dans The Moonstone (1868) de Wilkie Collins - Constance Collin (Cahiers Victoriens et Edouardiens)
The Moonstone was written in 1868, that is to say ten years after the Sepoy Mutiny of 1857-1858, still very present in the Victorian minds. It opens on a scene which takes place in a barbaric India, which seems to indicate that wilderness and confusion can only stem from foreignness. Indeed, the mystery is first and foremost that of the Indian diamond, stolen by a British colonel and then left as a legacy to his niece. If the plot evolves around strange and magical events and around the superstitions and legends that surround the stone, it mainly takes place on the West Yorkshire coast, in the house of the respectable Verinder family. This association between the ordinary and the extraordinary is quite relevant. By destroying the frontiers between the two, between what is known and what is unknown, what is foreign and what is domestic, what is strange and what is familiar, Collins turns Victorian representations upside down and poses the problem of definition and identity. The characters endlessly look for some kind of order and stability in a world the laws of which are constantly moving like the Shivering Sands of the coast. The structure of the novel itself reflects this dichotomy between order and disorder, since the mystery is solved through an experiment which belongs only partially to the rational means of investigation of the police and the law. The text thus becomes foreign to its own rules and conventions, and the reader must struggle to make it his/her own way.